The Consumer is not Necessarily a Citizen - Murphy, John W. (Sociologija. Mintis ir veiksmas, 2004)
Civil society is a remedy for the alienation that has been spawned by the market. Because the market has been differentiated categorically from civil society, the intersubjective origin of this economic regulator has been seriously distorted. Hence returning organizations to their base in civil society can have a very positive impact on the development of citizens. For example, when order is established on this foundation, persons have intimate knowledge of one another, build their relationships on interpersonally validated trust, and generate solidarity through their regular intervention into public space. As a result, associations that are grounded in civil society provide persons with a terrific sense of security. Constant engagement that encourages persons to defend one another is essential to the creation and preservation of an open and free society. This intervention is a virtue, rather than a nuisance. Consumers are crippled in this respect, and thus are incapable of achieving any security. There are no lasting relationships at the marketplace, but instead tenuous friendships that may have to be sacrificed at any moment to the demands of the so-called bottom line. Citizenship, on the other hand, cannot be this ephemeral. Therefore, democracy is in serious trouble in modern societies, if the citizen is replaced by the consumer. For without trust, mutual defense, and collective responsibility, a society is condemned to devolve into a morass of accusations, suspicions, and insecurities. None will assume that there is any benefit to engaging others in a long-term, collective project. Why, therefore, should society exist at all?
Keywords: civic society; alienation; consumer; Keynes; neoliberalism; ekonomics; Hayek